MAIN ISSUES TO BE RESOLVED IN ORGANIZING THE MOVEMENT OF PASSENGER TRAINS - Bozorov R.Sh.; Boboev D.Sh. (PEDAGOGS, 2025)
This article briefly describes the mathematical model of passenger flow planning in railway transport. Also, the factors affecting the speed of trains are known, which can be divided into the classification of factors affecting fuel consumption and throughput. The speed of trains is directly related to the delivery time of goods. However, during transportation, the time spent by goods on trains is only one third of the delivery time. The remaining delivery time, including the time spent by goods at stations to perform technical and technological operations, is not directly related to the speed of travel. The speed of trains is studied in terms of maximum permissible, traffic, technical, section, route speeds. Speed, like all elements of the transport process technology, is divided into two types. One is regulatory and technological documents regulating the speed, and the second is their implementation. Currently, more attention is paid to the development of regulatory technological documents than to their implementation.